2017
DOI: 10.1371/journal.pone.0179448
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of mother-to-child transmission of HIV: Postpartum adherence to Option B+ until 18 months in Western Uganda

Abstract: Since 2012, the WHO recommends Option B+ for the prevention of mother-to-child transmission of HIV. This approach entails the initiation of lifelong antiretroviral therapy in all HIV-positive pregnant women, also implying protection during breastfeeding for 12 months or longer. Research on long-term adherence to Option B+ throughout breastfeeding is scarce to date. Therefore, we conducted a prospective observational cohort study in Fort Portal, Western Uganda, to assess adherence to Option B+ until 18 months p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
2
19
2
Order By: Relevance
“…Our analysis shows that fewer than two-thirds of mothers selfreported complete adherence to ART at 18-24 months postpartum period. Even though a 100% rate of postpartum adherence is desirable, the 64% adherence level in this study is higher than the rate reported among postpartum mothers in a study in western Uganda [12] and in SSA [5]. Of concern, however, is the decline in the level of adherence among these women relative to the level reported during pregnancy [17].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our analysis shows that fewer than two-thirds of mothers selfreported complete adherence to ART at 18-24 months postpartum period. Even though a 100% rate of postpartum adherence is desirable, the 64% adherence level in this study is higher than the rate reported among postpartum mothers in a study in western Uganda [12] and in SSA [5]. Of concern, however, is the decline in the level of adherence among these women relative to the level reported during pregnancy [17].…”
Section: Discussioncontrasting
confidence: 58%
“…Existing evidence suggests that adherence rate decline during the postnatal period after peaking during pregnancy [9][10][11]. Also, studies conducted in Uganda and Zambia suggest that adherence rate is higher among pregnant women compared to breastfeeding women [12][13][14]. Younger age, alcohol and tobacco use, higher parity, and postpartum depression are among the main factors associated with non-adherence to ART [15,16], while disclosure and partner support facilitate adherence [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding factors that positively influenced maternal level of adherence to infants NVP prophylaxis regimen dispensation from 0-6 weeks, this study found maternal age and believe about the effectiveness of NVP in prevention of vertical transmission of HIV associated with maternal adherence. Specifically, relatively older mothers years of age were found to have higher likelihood of adherence than their counterparts who were aged [15][16][17][18][19] years. This might be due to the possibility that older mothers have accumulated more health knowledge than their younger counterparts, therefore have more HIV/AIDS illness experience and better cues to action.…”
Section: Discussionmentioning
confidence: 93%
“…A systematic review of both qualitative and quantitative studies on barriers and facilitators of ART adherence among HIV positive adults found that poor knowledge of HIV/AIDS & PMTCT services, ART and its associated demands negatively affects adherence to ART [15]. A Ugandan cross-sectional study found high levels of maternal non-adherence to ART and concluded that younger age, low parity, lower travel costs were positively associated maternal adherence, however quality of statistical analysis made the validity of the results questionable [16]. Disclosure of HIV/AIDS status to a spouse and the ART treatment support provided by spouse to women tend to improve ART adherence, and retention in ART program, however fear of negative consequences women might experience from the spouse was found to be barrier to adherence to ART [15].In a South African cross-sectional study that used reported maternal adherence to infants prophylaxis regimen at six weeks postpartum, maternal adherence to ART prior to delivery was associated with 80% reduction in non-adherence to infant's NVP prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…To reach the ambitious targets of EMTCT, ART adherence and programme retention are critical; unfortunately, both present unique challenges over the course of pregnancy and breastfeeding [65‐68]. In their review of the literature, Stover, et al estimated that maternal PMTCT retention to ART programmes at 80% at time of delivery [47].…”
Section: Resultsmentioning
confidence: 99%